2) Sejam f(x) = 2x + 1 e g(x) = 3x + 1. Então
f(g(3)) - g(f(3)) é igual a: *
Soluções para a tarefa
Respondido por
27
Resposta:
-1
Explicação passo-a-passo:
g(x)=3x+1
g(3)=3.3+1
g(3)=10
f(10)=2x+1
f(10)=2.10+1
f(10)=21
logo f(g(3))=21
f(3)=2x+1
f(3)=2.3+1
f(3)=7
g(7)=3x+1
g(7)=3.7+1
g(7)=21+1
g(7)=22
logo g(f(3))=22
f(g(3))-g(f(3))=21-22= -1
Perguntas interessantes
Geografia,
10 meses atrás
Inglês,
10 meses atrás
Matemática,
10 meses atrás
Contabilidade,
1 ano atrás
Português,
1 ano atrás
Contabilidade,
1 ano atrás
Administração,
1 ano atrás